Advances in environmental accounting & management : social and environmental accounting in Brazil - Belal, Ataur Rahman; Cooper, Stuart, 1970-; Freire, Fátima de Souza (Advances in environmental accounting & management, 2017)
Vol 6 of Advances in Environmental Accounting & Management aims to advance knowledge of the governance and management of corporate environmental impacts and the accounting for these, including issues related to measurement, valuation, and disclosure. It is particularly relevant for accounting practitioners, investors and other stakeholders of the financial and social consequences of corporate environmental impacts.